Franz Karl Naegele (1778-1851) - K. N. Grigorieva (IRBIS LLC, 2022)
The date of the expected birth is important not just for future parents but rather for obstetricians and gynecologists. Midwives and doctors of all generations know and apply the Naegele rule, based on the dates of menstruation for determining duration of pregnancy. Despite the advent of ultrasound diagnostics that provides a more accurate method to calculate an expected date of birth, up until now the Naegele rule remains relevant.